Coupled THM Modelling of Wellbore Stability with Drilling Unloading, Fluid Flow, and Thermal Effects Considered. (9th April 2019) - Jia, Shanpo; Wen, Caoxuan; Deng, Fucheng; Yan, Chuanliang; Xiao, Zhiqiang
Abstract : Both overbalanced drilling and underbalanced drilling will lead to the change of pore pressure around wellbore. Existing research is generally based on hydraulic-mechanical (HM) coupling and assumes that pore pressure near the wellbore is initial formation pressure, which has great limitations. According to the coupled theory of mixtures for rock medium, a coupled thermal-hydraulic-mechanical (THM) model is proposed and derived, which is coded with MATLAB language and ABAQUS software as the solver. Then the wellbore stability is simulated with the proposed model by considering the drilling unloading, fluid flow, and thermal effects between the borehole and the formation. The effect of field coupling on pore pressure, stress redistribution, and temperature around a wellbore has been analyzed in detail. Through the study of wellbore stability in different conditions, it is found that( 1 ) for overbalanced drilling, borehole with impermeable wall is more stable than that of ones with permeable wall and its stability can be improved by reducing the permeable ability of the wellbore wall;( 2 ) for underbalanced drilling, the stability condition of permeable wellbore is much higher than that of impermeable wellbore;( 3 ) the temperature has important influence on wellbore stability due to the variation of pore pressure and thermal stress; the wellbore stability can be improved with cooling drilling fluid for deep well. The present method can provide references for coupled thermal-hydraulic-mechanical-chemical (THMC) process analysis for wellbore.